2010
DOI: 10.1007/s00787-010-0126-4
|View full text |Cite
|
Sign up to set email alerts
|

Deficient maturation of aspects of attention and executive functions in early onset schizophrenia

Abstract: Word count of the Abstract: 220Word count of the text body: 5819 including the revised Appendix A 3 AbstractThe few existing long-term, neuropsychological follow-up studies of early-onset schizophrenia (EOS) patients have reported relative stability in some cognitive functions but abnormal developmental trajectories in verbal memory, set shifting, aspects of attention, and speed of information processing throughout late adolescence into early adulthood. The current 5-year followup study compared the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 84 publications
1
20
0
Order By: Relevance
“…In HC, we found that with increasing age, reaction time decreased across all networks, indicating improved performance in healthy subjects. These data, along with the existing literature (Fjell et al, 2012; Jepsen et al, 2010; Konrad et al, 2005), suggest a protracted developmental trajectory for attentional networks during adolescence.…”
Section: Discussionsupporting
confidence: 73%
“…In HC, we found that with increasing age, reaction time decreased across all networks, indicating improved performance in healthy subjects. These data, along with the existing literature (Fjell et al, 2012; Jepsen et al, 2010; Konrad et al, 2005), suggest a protracted developmental trajectory for attentional networks during adolescence.…”
Section: Discussionsupporting
confidence: 73%
“…They can lead to delays in the maturation of neuropsychological functions in affected children and adolescents and longterm neuropsychological deficits [1,2] as well as significant impairments in psychosocial functioning [3]. This makes schizophrenia one of the six leading causes of years lived with disability [4].…”
mentioning
confidence: 99%
“…The trajectories of cognitive deficits over the course of the disease are being debated, and one question has been whether schizophrenia involves neurodegeneration (Rund, ). To date, most longitudinal studies indicate a stable cognitive course in AOS (Bora, ; Rund et al., ), with a growing body of research suggesting a similar stability in EOS (Bombin et al., ; Frangou, Hadjulis, & Vourdas, ; Jepsen, Fagerlund, Pagsberg, Christensen, Nordentoft, et al., ; Juuhl‐Langseth, Holmen, Thormodsen, Oie, & Rund, ; Mayoral et al., ; Oie, Sundet, & Rund, ). However, the course of global cognition over the first years, as measured in composite scores, has yet to be reported in EOS.…”
Section: Introductionmentioning
confidence: 99%